Ritzerova mekdonaldizacija društva: Pomračenje uma, racionalnost i dehumanizacija savremenog svijeta / Ritzer's Mcdonaldization of Society: Eclipse of Reason, Rationality and Dehumanization of the Contemporary World - Aličković, Rifat (Pregled: časopis za društvena pitanja / Periodical for social issues, 2025)
The McDonaldization of society is the process by which the principles governing the operation of McDonald's restaurants become the principles guiding the functioning of society—education, politics, healthcare, administration, judiciary etc. These principles are efficiency, calculability, predictability, and control. Ritzer’s analysis begins with modern American society, though he notes that this is a process gradually encompassing the entire world. McDonaldization is not a unique global phenomenon – it is the outcome of a long process of modernization. The central feature of this process is a transformation in which objective reason—the belief that the world is governed by Reason regulating both social and natural phenomena—has been substituted by subjective reason - which is strictly concerned with calculations of utility, probability, and personal benefit. If in the past, an individual's goal was to align their reason with the objective order and submit to it, now, due to the inability to conceptualize such objectivity, the goal is to establish personal standards of behavior and goals achieved through utilitarian calculation. This overall orientation has shaped the institutional architecture of modern civilization, where the paradigmatic model of such a society, characterized by its inherent rationalization, is bureaucracy – but for Ritzer, it's McDonald's. While Ritzer acknowledges certain advantages of this process, it is ultimately the negative aspects that characterize this phenomenon as concerning and potentially dehumanizing.